A Clinical Trial on the Effect of Guduci (Tinospora Cordifolia (Willd) Miers) Satva along with Ksheera in Perimenopausal Symptoms (International Journal of Ayurveda and Pharma Research, 2022)
Perimenopause refers to the period around menopause. In Ayurveda it is considered as Rajakshaya, the transition period of body from predominance of Pitta dosha to Vatadosha which is characterized by aggravation of Vata, alteration of Pitta and Kaphadosha. It is included as a Swabhavikavyadhi in Ayurveda. Management of Dhatukshaya, Rasayana, Balya and Rasa- Raktha Prasadana treatments are seen beneficial in this condition. Guduci is one among Rasayana drugs mentioned in Ayurveda. The drug Guducisatva taken for the study is from the classic Yogaratnakara and has Dhatukrith and Vayastapana property. The objective of the study was to evaluate the effect of 1g Guduci Satva along with Ksheera (25ml boiled and lukewarm) in perimenopausal symptoms. Females in the age group 40-50 years with perimenopausal symptoms were selected for the study from the OPD of Prasutitantra-striroga, GAVC Hospital, Tripunithura as per the inclusion criteria. Study tools are clinical case proforma and Greene Climacteric scale score above 30. Drug was given orally in the dose of 1g twice along with 25ml Ksheera one hour before food. Duration of administration was 30 days and assessment was taken on 0th day, 31st day and 60th day. Results were analysed statistically by Wilcoxon's signed rank test and Friedman’s test. The study result is highly significant after treatment with P value